Development of naturally carbonated fermented whey fruit-juice based beverage - Kaur, Simarjit; Bhise, Suresh Rajabhau; Kaur, Amarjeet; Minhas, KS (Indian Journal of Dairy Science, 2018)
Naturally carbonated fermented whey fruit-juice based beverage were prepared by blending cheese whey with pineapple and strawberry juice after inoculating Clavispora lucitaniae yeast culture @ 0.5% v/v and allowed to ferment at 35±1oC temperature for 36 hours aerobically. Standardization of beverage was done by using 16, 15, 14, 13 and 12oBrix TSS levels with 15, 20, 25 and 30% fruit juice concentration. Beverage with 12oBrix TSS and 30% juice concentration was selected as best combination for storage study under refrigerated (4±1oC) and ambient (25±5oC) conditions and evaluated for physico-chemical, microbiological and sensory analysis for 90 days of storage periods. There was significant decrease in brix:acid ratio (p-value: 0.00004 at ambient; 0.00003 at refrigeration), total sugars (p-value: 0.0253 at ambient; 0.0214 at refrigeration), and ascorbic acid (p-value: 0.0006 at ambient; 0.0023 at refrigeration) whereas TSS, pH, reducing sugar, color and lactose content were decreased insignificantly over the ambient and refrigeration storage period for cheese whey beverage blended with pineapple juice. While acidity, alcohol and CO2 content were increased insignificantly over the ambient and refrigeration storage. Beverage stored at refrigeration temperature was found more acceptable than the beverage which was stored at ambient temperature irrespective of all types of beverages. Cheese whey beverage blended with strawberry juice obtained higher overall acceptability scores than the cheese whey beverage blended with pineapple juice. The beverage at refrigeration ambient storage was found acceptable upto 90 and 60 days respectively. The beverage obtained had naturally produced CO2 and little alcohol content added effervescence, sparkle, tangy taste and flavouring characteristics.